Effectiveness of circuit interval training and physiotherapy health education on anthropometric measurements and quality of life among obese women with polycystic ovary syndrome- a randomised controlled trial - S. Christy Sopna; Beulah Jebakani D.; Jayavani R. L.; Sabita P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The objective was to assess the effectiveness of circuit interval training and physiotherapy health education on anthropometric measurements and quality of life (QOL) among obese women with PCOS. Methods: The study is a parallel group randomised controlled trial among 40 obese women diagnosed with PCOS based on Rotterdam criteria and conducted in obstetrics and gynaecology Physiotherapy centre, IGMC&RI, Puducherry. Allocation of participants to group A and group B done using permutated block randomization by an independent physiotherapist. Group A(n=20) received the conventional treatment and Group B (n=20) received the circuit interval training for 6 weeks. Results: The outcome values obtained were calculated by the software SPSS 26. The power of the study is 80%. P<0.05 was considered a significant difference and 95% confidence. There was a significant improvement in the pre and post-test values of anthropometric measurements (BMI and WHR) within the experimental group. The minimal clinically important difference (MCID) of 1.03 points in BMI, 0.019 in WHR, and 0.018 in WHtR, which was higher than the MCID of the control group was observed between the groups. The results show that circuit interval training is effective in improving the anthropometric measurements and quality of life obesity was found to have a negative correlation with the quality of life, implying that increased weight reduces the quality of life in PCOS women. Conclusions: Circuit interval training along with physiotherapy health education, has a positive impact on improving anthropometric measurements such as BMI, waist circumference, and metabolic parameters over time.